Search 75,764 tutors
FIND TUTORS
Ask a question
0 0

Composition of Functions

Tutors, please sign in to answer this question.

1 Answer

Given:     f(x) = x - 4          and          g(x) = 3x - 4

(fοg)(x) = f(g(x))

            = f(3x - 4)              replace every x in f(x) with '3x - 4'

            = (3x - 4) - 4

            = 3x - 4 - 4

            = 3x - 8

(gοf)(x) = g(f(x))

            = g(x - 4)                  replace every x in g(x) with 'x - 4'

            = 3(x - 4) - 4

            = (3·x - 3·4) - 4

            = 3x - 12 - 4

            = 3x - 16